Sucesso em projetos: uma análise sobre a contribuição do comportamento intraempreendedor - Novaes, Graziela Fontes (2021)
Recent studies reveal the positive relationship between intrapreneurial behavior and project success, but there are gaps for a better understanding of how this relationship occurs. This research objective is to analyze how the intrapreneurial behavior of a project team members contributes to project success. This research is justified due to the need to raise the conditions for projects to be successful, as companies seek better performance, innovation and competitive advantage. The methodology used consists of a qualitative analysis, given through a case study in a large national company. Data were collected from three project teams, through the application of questionnaires that measure the projects success and intrepreneurial behavior, as well as selected projects document’s analysis. This study results demonstrate the contributions of intrapreneurial behavior, its dimensions and organizational factors that facilitate this behavior for the projects success. Contributions include achieving results and financial gains, continuous improvement of processes, team involvement and engagement, driving change, among others. Furthermore, it associates the contributions pointed out by the interviewees with the dimensions of project success portrayed in the literature. In a practical way, this research points out possibilities for companies and their respective human resources sectors to be able to guarantee the commitment of their employees with the projects success. Academically, this work contributes to increasing synergies between the entrepreneurship and project management fields. This study is part of the PPGP-UNINOVE Project Management research line, in the context of the research project on Entrepreneurial Guidance in Organizations and Projects, and the project financed by the CNPq Universal Notice entitled Effects of Entrepreneurship on Project Success: a study on dimensions of Entrepreneurial Orientation and Intrapreneurship in the context of projects.